Protective effect of vitamin C and lycopene on the in vitro fertilization capacity of sex‐sorted bull sperm by inhibiting the oxidative stress - Zhang, Pei‐Pei; Wang, Jing‐Jing; Li, Chong‐Yang; Hao, Hai‐sheng; Wang, Hao‐Yu; Du, Wei‐Hua; Pang, Yun‐Wei; Zhao, Shan‐Jiang; Zou, Hui‐Ying; Hao, Tong; Yang, Sha; Ruan, Wei‐Min; et al. (Reproduction in domestic animals, 2020)
The fertilization capacity of sex‐sorted sperms is seriously decreased, which inhibits its wide application. However, little information is still available about the effect of vitamin C (VC) and lycopene (Lyc) on the fertilization capacity of sex‐sorted bull sperm. In this study, the washing medium and fertilization medium of sex‐sorted sperm from three bull individuals were supplemented with different concentrations of VC (0, 1 × 10–3, 1 × 10–4, 1 × 10–5, 1 × 10–6 M) or Lyc (0, 1 × 10–4, 1 × 10–5, 1 × 10–6, 1 × 10–7). After washing twice and incubation for 1.5 hr, the malondialdehyde (MDA) level, phosphatidylserine (PS) translocation, membrane potential (Δψm) and IVF (in vitro fertilization) ability of sex‐sorted sperm were investigated. For the sex‐sorted sperm of bulls A, B and C, 1 × 10–3 M VC or 1 × 10–4 M Lyc treatment significantly decreased their MDA levels and PS translocation and increased their Δψm levels and cleavage rates after IVF. When blastocysts were concerned, 1 × 10–4 M Lyc significantly improved the blastocyst rates and their IFN‐tau expression of bulls A and C. In conclusion, supplementation of 1 × 10–3 M VC or 1 × 10–4 M Lyc in washing and fertilization medium contributed greatly to improving the fertilization capacity of sex‐sorted bull sperm during IVF procedure.